2017
DOI: 10.1177/1457496917701670
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing the Effects of Psychotherapy on Weight Loss after Laparoscopic Gastric Bypass or Laparoscopic Adjustable Gastric Banding in Patients with Borderline Personality Disorder: A Prospective Study

Abstract: Background and Aims: Personality disorders are frequently associated with eating disorders in obese patients and may negatively affect weight loss and maintenance after bariatric surgery. This non-randomized study aimed to assess the effects of different psychotherapeutic interventions on weight loss in a sample of patients with borderline personality disorder who underwent laparoscopic gastric bypass or laparoscopic adjustable gastric banding.Materials and Methods: A total of 153 bariatric patients meeting bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
60
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(60 citation statements)
references
References 42 publications
(52 reference statements)
0
60
0
Order By: Relevance
“…Numerous studies identified certain “high risk” groups to participate in psychosocial interventions, including seven studies identifying patients with maladaptive eating patterns, one study identifying individuals with body dissatisfaction despite substantial weight loss, six studies identifying individuals with psychosocial difficulties, three studies identifying individuals with lack of physical activity, four studies identifying patients with a past history of weight plateau or regain after weight loss attempts, and one study with patients presently deemed unsuitable to undergo surgery…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Numerous studies identified certain “high risk” groups to participate in psychosocial interventions, including seven studies identifying patients with maladaptive eating patterns, one study identifying individuals with body dissatisfaction despite substantial weight loss, six studies identifying individuals with psychosocial difficulties, three studies identifying individuals with lack of physical activity, four studies identifying patients with a past history of weight plateau or regain after weight loss attempts, and one study with patients presently deemed unsuitable to undergo surgery…”
Section: Resultsmentioning
confidence: 99%
“…Of the studies reviewed, 16 focused on preoperative interventions and 24 on post‐operative interventions . One study offered the intervention either before or after surgery, and three studies examined interventions delivered at time points both before and after surgery …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations